Enhanced pollutant removal from rural non-point source wastewater using a two-stage multi-soil-layering system with blended carbon sources: Insights into functional genes, microbial community structure and metabolic function - Qi Zhou; Sun, Haimeng; Jia, Lixia; Zhao, Liu; Wu, Weizhong (CHEMOSPHERE, 2021)
A two-stage multi-soil-layering system with blended carbon sources (MSL-BCS) was constructed at pilot scale for treatment of rural non-point source wastewater. Results showed the MSL-BCS system had effective removal efficiencies with 64% of TN and 60% of TP, respectively. The addition of BCS could result in higher (1.6-3.1 fold) denitrification gene abundances (nirS and nosZ) for enhancing denitrification. High-throughput sequencing approach revealed that the higher abundance (>50%) of Epsilonbacteraeotra (Genus: Sulfuricurvum, Family: Thiovulaceae, Class: Campylobacteria, Phylum: Epsilonbacteraeota) enriched in the surface of BCS, which suggested that Epsilonbacteraeotra are the keystone species in achieving nitrogen removal through enhancing denitrification at oligotrophic level. KEGG analysis indicated that BCS might release some signaling molecules for enhancing the energy metabolism process, as well as stimulate the enzyme activities of histidine kinase, glycogen phosphorylase and ATPase, and thereby the denitrification processes were strengthened in MSL-BCS system. Consequently, this study could provide some valuable information on the removal performance and mechanism of engineering MSL systems packed with BCS to govern the rural wastewater treatment. (C) 2021 Elsevier Ltd. All rights reserved.